Health Insurance Literacy Among International College Students: A Qualitative Analysis - Adegboyega, Adebola; Nkwonta, Chigozie; Edward, Jean (Journal of International Students, 2020)
In this qualitative descriptive study, we examine health insurance literacy among a group of international college students. They were recruited from a public, co-educational Southeastern university in the United States during the fall semester of 2016 to participate in semistructured interviews. Data were gathered through a demographic questionnaire, two focus group discussions, and individual interviews. Interview sessions were audio-recorded, transcribed, and analyzed using a thematic analysis approach. Three themes emerged, including knowledge of health insurance options and benefits information, affordability, and unmet expectations. These findings show the need for higher education institutions to develop a plan to integrate international students into U.S. health care. International students are a vulnerable population; therefore, increasing health insurance literacy is vital to making an optimal health insurance choice, improving access to health care, and using health care efficiently. Future research should tailor educational interventions to mitigate poor health insurance literacy among international college students.